1974
DOI: 10.2135/cropsci1974.0011183x001400040026x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Oat Kernel Characteristics Within the Panicle1

Abstract: Oat (Avena sativa L.) investigations are of current interest because of the high quality protein present in the oat groat. In this study, groats were analyzed individually from single panicles selected from three replicates each of ‘Dal,’ ‘Froker,’ and ‘Orbit’ oats grown in the nursery and in the greenhouse. Grain weight, groat weight, groat percent, protein percent, and protein content per groat were determined, and relative position on the panicle was recorded. Within a panicle, groat weight decreased and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0
2

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 0 publications
4
25
0
2
Order By: Relevance
“…Furthermore, the position of the panicle with highest cell number in our study (Fig. 1) also tended to produce the largest and heaviest grains in the study of Youngs and Shands (1974). Results from an additional experiment in the greenhouse with the conventional oat cultivar Virma and the naked Rhiannon further supported the finding that secondary grains are consistently lighter (Table 1), also in agreement with our preliminary finding on lower cell number.…”
Section: Vol 13 (2004): 163-169supporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the position of the panicle with highest cell number in our study (Fig. 1) also tended to produce the largest and heaviest grains in the study of Youngs and Shands (1974). Results from an additional experiment in the greenhouse with the conventional oat cultivar Virma and the naked Rhiannon further supported the finding that secondary grains are consistently lighter (Table 1), also in agreement with our preliminary finding on lower cell number.…”
Section: Vol 13 (2004): 163-169supporting
confidence: 91%
“…Similarly, growth of primary grain exceeds growth of secondary and tertiary grains (Youngs and Shands 1974, Tibelius and Klinck 1987, Doehlert et al 2002. In fact, the single kernel weight of primary grain seems to be dependent on number of florets in spikelet.…”
Section: Rajala a And Peltonen-sainio P Intra-plant Variation In Dementioning
confidence: 98%
See 2 more Smart Citations
“…Studies (Berry 1920 al. 1952;Youngs and Shands 1974;Doehlert et al 2002) indicated that primary kernels from three-kernel spikelets are larger than primary kernels from two-kernel spikelets. Secondary kernels from three-kernel spikelets are about the same size as primary kernels from one-kernel spikelets, both of which are larger than secondary kernels from two-kernel spikelets.…”
mentioning
confidence: 99%